1998
DOI: 10.1111/j.1471-0528.1998.tb10093.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in women with von Willebrand's disease or factor XI deficiency

Abstract: Objective To assess the obstetric outcome in women with von Willebrand's disease or factor XI Setting Haemophilia Centre and Haemostasis Unit, The Royal Free Hospital.Population Women with von Willebrand's disease (n = 3 1) and with factor XI deficiency (n = 11) registered at the Royal Free Hospital Haemophilia Centre who had had a pregnancy within the previous 17 years (1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996), including 84 in women with von Willebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
366
3
15

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(401 citation statements)
references
References 29 publications
17
366
3
15
Order By: Relevance
“…Given the case selection, the large majority of these women had a severe phenotype, with FVIII:C and/or VWF basal levels less than 20 IU/dL (Table I), at variance with women previously reported in other studies. 4 In mild cases of VWD, normalization of FVIII and VWF activities at the end of pregnancy is usually observed and prophylactic treatment is seldom required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the case selection, the large majority of these women had a severe phenotype, with FVIII:C and/or VWF basal levels less than 20 IU/dL (Table I), at variance with women previously reported in other studies. 4 In mild cases of VWD, normalization of FVIII and VWF activities at the end of pregnancy is usually observed and prophylactic treatment is seldom required.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 While patients with mild deficiency usually show a spontaneous complete correction of basal low factor VIII (FVIII) and von Willebrand factor (VWF) levels during pregnancy, patients with dysfunctional (type 2) or severe (type 3) VWD usually require replacement treatment to avoid immediate or delayed bleeding. 3,4 Despite the fact that several studies have addressed the risk of bleeding at parturition, very few have evaluated FVIII and VWF changes during pregnancy, the bleeding risk and treatment modality in relationship to the specific VWF gene mutations and response to desmopressin. We recently reported a favorable clinical outcome at delivery using desmopressin in a few women with VWD associated with C1130F mutation 5 and R1205H (VWD Vicenza), 6 in whom FVIII and VWF increased poorly during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated individual medical comorbidities, such as pre-existing asthma, hypertension, malignancy, chronic ischaemic and congenital heart disease, chronic renal disease, systemic lupus erythematosus, hypercoagulability states, human immunodeficiency virus and diabetes mellitus, to be associated with both severe maternal morbidity and mortality, 25,153,[162][163][164][165][166][167][168] but the extent of the population risk attributable to medical comorbidities as a whole in the UK has not previously been quantified. Uptake of antenatal care was found to be poorer among women with medical comorbidities in our study population, which could increase the adverse effects associated with these conditions.…”
Section: Conclusion and Implications For Policy And Practicementioning
confidence: 99%
“…PPH can be prevented or its severity can be moderated by educating women and their providers [8]. While delayed or secondary PPH is rare, occurring after <1% of deliveries [10,11], it has been reported in 20-25% of women with VWD [12,13], 2-11% of haemophilia carriers [14,15] and 24% of women with factor XI deficiency [14]. Carriers are another significant and often neglected member of the global bleeding disorder family.…”
Section: Introductionmentioning
confidence: 99%